Nasal polyps and its histopathological classification: A retrospective study - Jitendra Pratap Singh Chauhan; Ritu Gupta; Abhay Kumar (Asian Journal of Medical Sciences, 2023)
Background: The diagnosis of nasal polyp is made according to clinical and radiological criteria, while histopathologic examination is important for an accurate diagnosis. Histological classification of nasal polyps and its clinical implications are very rarely reported in the literature. Aims and Objectives: The aim of this study was to study clinical presentation and site of occurrence of nasal polyps and histologically classify nasal polyps in relation to studies published in the literature. We classified the histological changes as described by Davidson and Hellquist. Materials and Methods: Based on the inclusion and exclusion criteria, the 315 subjects were included in our study, which include eosinophilic polyp, fibro-inflammatory polyp, polyp with sero-mucinous gland hyperplasia, and polyp with stromal atypia. Results: Sinonasal polyps can be classified in the following way histologically: edematous or eosinophilic polyp 189 cases (60%); fibro-inflammatory polyp: 66 cases (21%); polyp with seromucinous gland hyperplasia: 35 cases (11%), polyp with stroma atypia: no case (0%), and fibrotic 25 cases (8%). Conclusion: We concluded that the nasal polyps mainly present as an edematous or eosinophilic pattern on histopathological examination. Studies on the histopathology of nasal polyps would help us to understand this disease more appropriately for treatment plan. Further differentiation of nasal polyps may help to develop new therapeutic strategies that are tailored according to the respective group.